Pengukuran Kinerja Perbankan Dengan Metode CAMEL - Akramunnas, Akramunnas; Kara, Muslimin (Universitas Islam Negeri Alauddin Makassar, 2019)
This research article reviews the performance comparison of conventional BRI and BRI sharia banking using the CAMEL method. The sample in this study is the Financial Report data in the form of financial statements of BRIand BRI sharia which have been published in Bank Indonesia in 2013-2017. Data were analyzed using Independent sample t-test to test whether there were statistically significant differences between the financial performance of BRI and BRI sharia. Research Results show (1) BRI banking performance in the aspect of capital and management quality are in the healthy category; profitability factors and liquidity aspects Very healthy; (2) BRI sharia performance are: Capital factors and quality in the management arein category Unhealthy; Rentability factors are in the category of Fair enough; Assessment of liquidity is in the healthy category; (3) Theres is no significant difference between the value of CAR, and the value of Loan to Deposit Ratio (LDR) / Financing to Deposit Ratio (FDR) in BRI and BRI sharia; there are significant differences between the value of Non Performing Loans (NPL), Non Performing Finance (NPF) and Return on Assets (ROA) at BRI and BRI shariaKeywords: Banking Performance, Camel, BRI, BRI ShariahArtikel Penelitiaan ini mengulas perbandingan kinerja Bank BRI dan BRI Syariah dengan menggunakan metode CAMEL, Sampel yang digunakan adalah data laporan keuangan berupa laporan keuangan BRI dan BRI Syariah yang telah dipublikasikan di Bank Indonesia tahun 2013-2017. Data dianalisis menggunakan Independent sample t-test untuk menguji perbedaan signifikan antara kinerja keuangan BRI dan BRI Syariah. Hasil Penelitian menunjukan; (1) Kinerja perbankan BRI pada aspek permodalan dan aspek kualitas manajemen berada dalam kategori sehat; aspek rentabilitas dan aspek liquiditas sangat sehat; (2) Kinerja BRI Syariah adalah: faktor permodalan dan likuiditas berada dalam kategori sehat; pada aspek kualitas asset dalam kategori pengelolaan manajemen kurang sehat; faktor rentabilitas berada dalam kategori cukup sehat. (3) Tidak ada perbedaan signiikan antara nilai CAR dan nilai Loan to Deposit Ratio (LDR) /Financing to Deposit Ratio (FDR) pada BRI dan BRI Syariah; ada perbedaan signifikan antara nilai Non Performing Loan (NPL), Non Performing Finance (NPF), Net Profit Margin (NPM) dan Return On Assets (ROA) pada BRI dan BRI Syariah. Kata Kunci: Kinerja Perbankan, Camel, BRI, BRI Syariah